SISTEM KOORDINASI KERJA FRONT OFFICE DEPARTMENT DALAM PENANGANAN CHECK-IN DAN CHECK-OUT DI ALLIUM BATAM HOTEL - Ferdinando Try Gunawan; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to determine about to find out work coordination system of FrontOffice Department in handling the check-in and check-out at Allium Batam Hotel.Coordination is an integration process activities that aims to produce an action toachieve common goals in an organization. Every leader need to coordinate theactivities to the organization members by given in completing the task. With the clearinformation and proper communication, and division of work to subordinate individualwill do the work in accordance with the authority received. Without any coordination otthe work of individual employees then the company’s goals will not be achieved. Thisresearch to make use qualitative method to analysis set of case, which to become thekey informan in this research as much as seven people’s. That is Front Office Manager,Night Duty Manager, Bell Captain, Front Office Supervisor, Guest Relation Officer,Reception and Bellboy. Sources were obtained through observation, interview, anddocumentation. Based on result of this research, the conlusions of this research arework coordination from Front Office Department has been done, but still needs to beimproved raising required so that coordination will be better in the future.Keywords : Coordination, Check-In, Check-Out